(untitled) (JONAH : Journal of Nursing and Homecare, 2024)
Dementia is a term used for a variety of diseases that cause permanent changes in the brain, characterized by cognitive impairment that affects memory. Brain gym therapy is a series of simple movements that can combine all parts of the brain to improve cognitive abilities. The purpose of this case study is to describe the application of brain gym therapy to improve cognitive function in elderly people with dementia. The research method used was descriptive with a case study approach using 2 subjects, carried out on April 10 - April 16, 2023. The subjects in this study were dementia patients with the criteria for a definite cognitive impairment score. The results of this case study showed an increase in cognitive function in subject I initial cognitive function 13 points to 15 points (definite cognitive impairment). In subject II initial cognitive function 14 points to 16 points (definite cognitive impairment). Regular brain gym therapy can improve cognitive function, because the way brain gym therapy works optimizes oxygen supply and blood flow to the brain, thereby providing adequate stimulation to brain structures. To maintain and improve cognitive function in both subjects, PSTW officers can guide and facilitate brain gym therapy.